RECOMMENDATION SYSTEM TO SELECT A MAJOR OF VOCATIONAL SCHOOL USING DECISION TREE - Ardiansyah Risko Anwari; Sukirman, Sukirman (Jurnal Teknik Informatika (Jutif), 2024)
A recommendation system is a tool that can be used to provide suggestions to users about something they are interested in, such as products, content, music, movies, or even majors at school. When registering for majors at vocational high school (SMK), some students sometimes difficult to select major based on their interests and abilities. This study aims to develop a recommendation system to select major in SMK, so that it can help prospective students choose majors according to their abilities. The method used is Research and Development (R&D), using the waterfall development model which consists of several stages, namely requirements analysis, system design, design implementation, and system testing. The algorithm used to recommend choices is a decision tree, a predictive model that maps input data to output targets based on a series of decisions or separation rules. The parameters used to recommend the selection of majors are the value data of last year's applicants. The evaluation was carried out using the system usability scale (SUS) involving 25 participants (17 males and 8 females) aged from 14 to 16 years old. Based on the analysis carried out, the results showed that SUS score is 89.7, which means that included to the excellent category in measuring adjective ranges, and acceptable in the acceptability scale. Thus it can be concluded that this department recommendation system is usable or can be used to provide advice to students in selecting a major in SMK.